Combined experimental and theoretical DFT study of molecular nanowires negative differential resistance and interaction with gold clusters - Zális, S; Kratochvilova, I; Zambova, A; Mbindyo, J; Mallouk, T E; Mayer, T S (The European physical journal. E, Soft matter, 2005)
Electric-field-assisted assembly has been used to place rod-shaped metal nanowires containing 4-[[2-nitro-4-(phenylethynyl) phenyl] ethynyl] benzenthiol molecules onto lithographically defined metal pads. These junctions exhibited negative differential resistance. The quantum chemical approach was used to compare the properties of Au-bonded 4-[[2-nitro-4-(phenylethynyl) phenyl] ethynyl] benzenthiol molecule and a molecule that does not exhibit the negative differential resistance, Au-bonded 4-[[4-(phenylethynyl) phenyl] ethynyl] benzenthiol. The influence of the static electric field and charge variation were modelled for both systems.